Darkpop!: a arqueologia dos espectros e as encarnações dos fantasmas do gótico na cultura pop - Caetano, Stella Mendonça (Universidade do Vale do Rio dos Sinos, 2025)
This thesis investigates how the Gothic, understood as a persistent aesthetic specter, updates itself within contemporary pop culture. To analyze the hybrid phenomena emerging at the intersection of the Gothic and mass culture—a noted gap in communication studies—this research proposes the concept of Darkpop. The theoretical framework is grounded in Hauntology (Derrida, 1994; Fisher, 2012, 2022) to explore the (dys)chronological and repetitive persistence of the Gothic, arguing that it operates as a specter and an autophagic ecosystem. Methodologically, the study puts forward the Archaeology of Specters, a qualitative method that articulates Hauntology with Media Archaeology (Fischer, 2013; Zielinski, 2006; Ernst, 2001, 2013). This approach serves to excavate the "ghosts" (contemporary manifestations) and their past incarnations from the digital archive. The method is applied through the mapping of Darkpop phenomena (2020–2024) and an in-depth case study of the series Wednesday (Netflix, 2022), which is analyzed through its historical layers, cultural impact, and its relationship with aesthetic capitalism (Lipovetsky & Serroy, 2015). The thesis concludes that the Gothic persists and updates itself through Darkpop by functioning as a haunted, autophagic ecosystem, fueled by the tensions between the underground and the mainstream. Its main contributions are, therefore, the concept of Darkpop and the methodology of the Archaeology of Specters as tools for the analysis of spectral cultural phenomena in communication studies.
Keywords: Gótico; Assombrologia; Estudos de circulação; Cultura pop; Darkpop; Gothic; Hauntology; Circulation studies; Pop culture; ACCNPQ::Ciências Sociais Aplicadas::Comunicação